Effects of Linseed Oil or Whole Linseed Supplementation on Performance and Milk Fatty Acid Composition of Lactating Dairy Cows - Suksombat, Wisitiporn (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
The objective of this study was to determine the effects of linseed oil or whole linseed supplementation on performance and milk fatty acid composition of lactating dairy cows. Thirty six Holstein Friesian crossbred lactating dairy cows were blocked by milking days first and then stratified random balanced for milk yields and body weight into three groups of 12 cows each. The treatments consisted of basal ration (53:47; forage:concentrate ratio, on a dry matter [DM] basis, respectively) supplemented with 300 g/d of palm oil as a positive control diet (PO), or supplemented with 300 g/d of linseed oil (LSO), or supplemented with 688 g/d of top-dressed whole linseed (WLS). All cows were received ad libitum grass silage and individually fed according to the treatments. The experiment lasted for 10 weeks including the first 2 weeks as the adjustment period, followed by 8 weeks of measurement period. The results showed that LSO and WLS supplementation had no effects on total dry matter intake, milk yield, milk composition, and live weight change; however, the animals fed WLS had higher crude protein (CP) intake than those fed PO and LSO (p<0.05). To compare with the control diet, dairy cow’s diets supplemented with LSO and WLS significantly increased milk concentrations of cis-9, trans-11-conjugated linoleic acid (CLA) (p<0.05) and n-3 fatty acids (FA) (p<0.01), particularly, cis-9,12,15-C18:3, C20:5n-3 and C22:6n-3. Supplementing LSO and WLS induced a reduction of medium chain FA, especially, C12:0-C16:0 FA (p<0.05) while increasing the concentration of milk unsaturated fatty acids (UFA) (p<0.05). Milk FA proportions of n-3 FA remarkably increased whereas the ratio of n-6 to n-3 decreased in the cows supplemented with WLS as compared with those fed the control diet and LSO (p<0.01). In conclusion, supplementing dairy cows’ diet based on grass silage with WLS had no effect on milk yield and milk composition; however, trans-9- C18:1, cis-9, trans-11-CLA, n-3 FA and UFA were increased while saturated FA were decreased by WLS supplementation. Therefore, it is recommended that the addition 300 g/d of oil from whole linseed should be used to lactating dairy cows’ diets.